2016
DOI: 10.1007/s00222-016-0699-8
|View full text |Cite
|
Sign up to set email alerts
|

Local spectral gap in simple Lie groups and applications

Abstract: Abstract. We introduce a novel notion of local spectral gap for general, possibly infinite, measure preserving actions. We establish local spectral gap for the left translation action Γ G, whenever Γ is a dense subgroup generated by algebraic elements of an arbitrary connected simple Lie group G. This extends to the non-compact setting works of Bourgain and Gamburd [BG06, BG10], and Benoist and de Saxcé [BdS14]. We present several applications to the Banach-Ruziewicz problem, orbit equivalence rigidity, contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 61 publications
2
56
0
Order By: Relevance
“…This result is due to Bourgain and Gamburd for G = SO(3) [BG06], and to Benoist and de Saxcé in general [BdS14]. In joint work with Boutonnet and Salehi-Golsefidy, we have shown that the same holds if G is an arbitrary connected simple Lie group [BISG15]. In particular, the translation action Γ (G, m G ) is strongly ergodic, whenever Γ < G := SL n (R) is a dense subgroup whose elements are matrices with algebraic entries.…”
Section: Oe Rigidity For Actions Of Non-rigid Groupssupporting
confidence: 57%
See 1 more Smart Citation
“…This result is due to Bourgain and Gamburd for G = SO(3) [BG06], and to Benoist and de Saxcé in general [BdS14]. In joint work with Boutonnet and Salehi-Golsefidy, we have shown that the same holds if G is an arbitrary connected simple Lie group [BISG15]. In particular, the translation action Γ (G, m G ) is strongly ergodic, whenever Γ < G := SL n (R) is a dense subgroup whose elements are matrices with algebraic entries.…”
Section: Oe Rigidity For Actions Of Non-rigid Groupssupporting
confidence: 57%
“…As an application, it led to a continuum of mutually non-OE and Borel incomparable actions of SL 2 (Z), confirming a conjecture from [Th01,Th06]. It also motivated a "local spectral gap" theorem for dense subgroups of simple Lie groups in [BISG15].…”
Section: Introductionmentioning
confidence: 61%
“…In [HI15, Section 6], for every λ ∈ (0, 1], a concrete example of a strongly ergodic free action F ∞ (X λ , µ λ ) on a standard measure space was constructed using the main result of [BISG15]. The following open question is interesting in this respect.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…We finally exploit recent results of Boutonnet-Ioana-Salehi Golsefidy [BISG15] to construct, for every 0 < λ ≤ 1, examples of type III λ strongly ergodic free nonsingular actions of a free group on a standard probability space. It is shown in [BISG15, Theorem A] that for any (not necessarily compact) connected simple Lie group and any countable dense subgroup Λ < G with "algebraic entries" (e.g.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%